Selection of the Best Marketplace using SAW and WP Methods: A Case Study of Bekasi City - Hadistra, Esa; Supriyanto, Raden (Sistemasi: Jurnal Sistem Informasi, 2026)
In today’s digital era, e-commerce has made transactions between sellers and buyers easier by eliminating the need for face-to-face interaction. The abundance of available marketplaces often makes it difficult for consumers to choose the platform that best fits their needs. This study aims to provide recommendations for the best marketplace based on four key criteria: trust, user interface design, promotions, and product completeness. The Simple Additive Weighting (SAW) and Weighted Product (WP) methods were applied to support this decision-making process. The research was conducted on five popular marketplaces, with data collected through questionnaires distributed to 200 active respondents. Both SAW and WP methods were used to calculate the weight and score of each marketplace based on consumer preferences regarding the predefined criteria. The results show that Shopee ranked as the top marketplace, achieving the highest scores of 0.99 (SAW) and 5.77 (WP), due to its strengths in trust, promotional offers, and product variety. Tokopedia placed second, with scores of 0.98 (SAW) and 5.75 (WP), excelling in its more intuitive user interface design. Other marketplaces showed strengths in specific criteria but were unable to surpass Shopee and Tokopedia in the final scores. These findings provide valuable insights for consumers in selecting the most suitable marketplace for their needs, and for marketplace operators seeking to improve service quality based on consumer-prioritized criteria.